2019
DOI: 10.1515/cclm-2018-1107
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory medicine: health evaluation in elite athletes

Abstract: The need to evaluate the health status of an athlete represents a crucial aim in preventive and protective sports science in order to identify the best diagnostic strategy to improve performance and reduce risks related to physical exercise. In the present review we aim to define the main biochemical and haematological markers that vary significantly during and after sports training to identify risk factors, at competitive and professional levels and to highlight the set up of a specific parameter’s panel for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 211 publications
1
45
0
7
Order By: Relevance
“…The relationship between obesity, hypercholesterolemia and lipoprotein profile modifications is well known [156][157][158]. Additional and independent risk factor for CHD is represented by high lipoprotein (a) [Lp(a)] levels, studied in several patient groups [159][160][161]. The association between its plasma levels and the condition of childhood obesity is unclear [162].…”
Section: Cardiovascular Riskmentioning
confidence: 99%
“…The relationship between obesity, hypercholesterolemia and lipoprotein profile modifications is well known [156][157][158]. Additional and independent risk factor for CHD is represented by high lipoprotein (a) [Lp(a)] levels, studied in several patient groups [159][160][161]. The association between its plasma levels and the condition of childhood obesity is unclear [162].…”
Section: Cardiovascular Riskmentioning
confidence: 99%
“…Laboratory medicine plays a central role in sport and monitoring athletes' health [1,66,67]. Numerous scientific studies have shown that intense and prolonged exercise can cause metabolic adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of stress induced by intense physical exercise encompasses the quantification and measurement of the parameters of strength, speed, power, and physical recovery to allow the coach and the medical health staff to calibrate the right training program for each athlete [1]. Recently, the scientific community has considered it appropriate to study biomarkers [2][3][4][5][6][7] capable of preventing muscle injuries [8][9][10], infections [11][12][13], and cardiovascular or thrombotic pathologies [14,15] while, at the same time, highlighting hidden genetic pathologies [16][17][18] that could undermine the athlete's health.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is that in this phase the coagulation wave, amplified by the slowing of blood flow, could overwhelm the significantly reduced anticoagulant potential and occasionally trigger an episode of DVT, depending on the association to other circumstantial/environmental factors. 1,14…”
Section: Discussionmentioning
confidence: 99%
“…Among the effects of physical exercise on coagulation, the influence on protein C anticoagulant system and PC deficiency-related thrombophilic risk are still controversial. 1 Several studies describe the impact of physical activity (PA) on the coagulation system. 2,3 It is well known, that PA determines a shortening of the activated partial thromboplastin time (APTT) and an increase of the factor VIII.…”
Section: Introductionmentioning
confidence: 99%